1985
DOI: 10.1139/y85-020
|View full text |Cite
|
Sign up to set email alerts
|

Unusual potassium channels mediate nonadrenergic noncholinergic nerve-mediated inhibition in opossum esophagus

Abstract: Field stimulation of the circular muscle of the opossum esophagus produces a transient hyperpolarization (inhibitory junction potential, IJP) followed by an "off" depolarization. A similar nonadrenergic, noncholinergic (NANC) response in guinea pig taenia caecum has been shown to be due to an increase in the potassium ion permeability of the smooth muscle cell membrane. Double sucrose gap studies showed a decrease in resistance during the IJP, and a reversal at an estimated membrane potential of about -90 mV (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

1986
1986
1989
1989

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 0 publications
2
40
1
Order By: Relevance
“…These differed from the ij.ps recorded from body circular muscle (Daniel et al, 1983;Jury et al, 1985) in being smaller (cf: Table 2 and see Daniel et al, 1983;Jury et al, 1985) and lacking detectable after-depolarization (Figures 4 and 5). They were accompanied by a significant reduction in the magnitude of electrotonic potentials evoked by hyperpolarizing constant current pulses (Table 2 and Figure 4), indicating that there was a conductance increase.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…These differed from the ij.ps recorded from body circular muscle (Daniel et al, 1983;Jury et al, 1985) in being smaller (cf: Table 2 and see Daniel et al, 1983;Jury et al, 1985) and lacking detectable after-depolarization (Figures 4 and 5). They were accompanied by a significant reduction in the magnitude of electrotonic potentials evoked by hyperpolarizing constant current pulses (Table 2 and Figure 4), indicating that there was a conductance increase.…”
Section: Resultscontrasting
confidence: 56%
“…NANC-relaxation of gut muscle, whenever it has been analysed (Tomita, 1972;Bywater et al, 1981;Jury et al, 1985) is caused by increased potassium conductance. Our earlier studies showed that none of several established Kconductance blockers (apamin, tetraethylammonium, 4-aminopyridine or quinine) abolished the ij.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEA produced a biphasic response which could be attributed to a TTX-insensitive release from nerve endings as previously suggested by Kirpekar & Prat (1978) who reported TEA-induced noradrenaline release from sympathetic nerve endings of the cat spleen. Thus, if potassium channel activation were involved in f.s.r., such channels as in the opossum lower oesophageal sphincter (Jury, Jager & Daniel, 1985) must have properties different from those demonstrated in other non-vascular smooth muscle, e.g. guinea-pig taenia coli (Mass, 1981).…”
mentioning
confidence: 87%
“…Previous attempts to test this hypothesis by the use of apamin, a specific inhibitor of certain Ca2 +-activated potassium channels (Banks et al, 1979), and tetraethylammonium (TEA), a nonselective potassium channel blocker (Hille, 1984), were unsuccessful (Akbarali et al, 1986). However, the potassium channels implicated in relaxations evoked by field stimulation may be atypical, and resemble those described in the lower oesophageal sphincter of the opossum oesophagus (Jury et al, 1985) and guinea-pig circular muscle of the intestine (Yamanaka et al, 1985), in so far as they are not involved in maintaining resting membrane potential, or generation of non-adrenergic, non-cholinergic (NANC)-nerve mediated inhibitory junctional potentials in the guinea-pig taenia coli (Den Hertog & Jager, 1975). BRL 34915 ((+ )-6-cyano-3,4-dihydro-2,2-dimethyl-trans-4-(2-oxo-1 -pyrrolidyl)-2H-benzo (b) pyran-3-ol) and pinacidil (N"-cyano-N-4 pyridyl-N'-1,2,2-trimethylpropylguanidine), have recently been shown to open potassium channels in a number of smooth muscle preparations including guinea-pig taenia caeci (Weir & Weston, 1986a), rabbit aorta (Kreye & Weston, 1986;Cook et al, 1987;Soiitherton et al, 1987), rat uterus (Edwards et al, 1987), rat portal vein (Weir & Weston, 1986b); and rabbit mesenteric artery (Coldwell & Howlett, 1987).…”
Section: Introductionmentioning
confidence: 99%